The Effect of Multiple Hop and Jump Training (Hurdle Jumps) on the Leg Muscle Power of Volleyball Athletes in SMPN 11 Kota Bengkulu Extracurricular - Daffa Wahyu Al Hafiidh; Lina Pitaloka; Muhammad Iqbal Prima Harman; Yoga Apriansyah; Egot Saputra; Roni Syaputra (Educative Sportive, 2025)
This study aims to determine the effect of a 6-week multiple hop and jump training program (hurdle jumps) on the leg muscle power of volleyball extracurricular athletes at SMPN 11 Bengkulu City. This quantitative study utilized an experimental method with a One-Group Pretest-Posttest Design. The population and sample consisted of all 15 active volleyball extracurricular athletes, selected using total sampling. The instrument used to measure leg muscle power was the vertical jump test, recorded in centimeters (cm). Data were analyzed using the Shapiro-Wilk normality prerequisite test and the Paired Sample t-Test for hypothesis testing, with a significance level of $α = 0.05. The results showed an increase in the athletes' average vertical jump performance, where the mean pretest score of 47.6 cm increased to 53.2 cm in the posttest, yielding an average improvement of 5.6 cm. The statistical analysis using the Paired Sample t-Test obtained a t_{count} value of -8.451 with a significance value (p-value) of 0.000 < 0.05. Consequently, the null hypothesis (H_0) was rejected, and the alternative hypothesis (H_a) was accepted. The study concludes that the structured 6-week multiple hop and jump training program (hurdle jumps) has a positive and significant effect on increasing the leg muscle power of volleyball extracurricular athletes at SMPN 11 Bengkulu City.